2005
DOI: 10.1163/1568562054255709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bFGF incorporated into a gelatin sheet on wound healing

Abstract: Basic fibroblast growth factor (bFGF) is well known to promote the proliferation of almost all cells associated with wound healing. However, as the activation duration of bFGF is very short in vivo, we incorporated bFGF into an acidic gelatin hydrogel and studied the sustained release of bFGF in vivo. In addition, we investigated the effects of the acidic gelatin sheet containing bFGF on wound healing. To distinguish wound contraction from neoepithelialization, we measured both the wound area and neoepithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 36 publications
4
59
0
Order By: Relevance
“…In our animals, the MVD in the bFGF-GH group was significantly higher from d 7 onwards. Our results are consistent with previous reports [20,21], in which bFGF incorporated into gelatin sheets promoted neovascularization compared with controls. Angiogenesis is an absolute requirement for successful healing of anastomosis, regardless of the type of anastomosis [22].…”
Section: Discussionsupporting
confidence: 93%
“…In our animals, the MVD in the bFGF-GH group was significantly higher from d 7 onwards. Our results are consistent with previous reports [20,21], in which bFGF incorporated into gelatin sheets promoted neovascularization compared with controls. Angiogenesis is an absolute requirement for successful healing of anastomosis, regardless of the type of anastomosis [22].…”
Section: Discussionsupporting
confidence: 93%
“…Gelatin dissolves in water at 60°C then gels as the solution cools to room temperature (Young et al 2005). Gelatin is widely used in pharmaceutical and medical applications due to its biodegradable nature (Ikada and Tabata 1996;Miyoshi et al 2005).…”
Section: Gelatinmentioning
confidence: 99%
“…Concerning the gelatin hydrogel sheet in this study, Miyoshi et al [19] reported that this sheet could sustain the release of bFGF and the sheet impregnated with bFGF promoted wound closure, neoepithelialization and neovascularization in murine skin defects. Matsui et al [9] prepared gelatin granules homogenized from this gelatin sheet and reported that granules incorporating PRPr or bFGF released PDGF-BB or bFGF in good correspondence with its degradation.…”
Section: Discussionmentioning
confidence: 74%